Cytomegalovirus, adenovirus, and polyomavirus co-infection among pediatric recipients of allogeneic stem cell transplantation: Characteristics and outcome - Siriorn P. Watcharananan (2018)
ADV and PMV infection have increasingly been documented as significant complications following allo-HSCT. Despite increasing recognition, characteristics and outcome of CMV, ADV, and PMV viral co-infection remain obscured. In this study, a retrospective quantitative PCR analysis of ADV, PMV (BKV and JCV) was performed from pediatric patients' stored blood samples previously tested for CMV viremia after allo-HSCT. Clinical and virological characteristics and outcome among patients with and without viral co-infection were analyzed and compared. From 2001 to 2006, 219 blood samples from 69 patients were studied. Viral DNA was present in 119 samples (52.9%).The proportion of viremia was highest for BKV (30.6%), followed by CMV (20.9%), ADV (9.1%), and JCV (0.5%). Viral co-infection occurred in 17 patients (24.6%), with CMV/BKV as the most common type (11.6%), followed by CMV/ADV (4.3%) and ADV/BKV (2.9%). From multivariate analysis, factors associated with viral co-infection were acute GVHD (OR 4.57; 95% CI 1.9-10.96, p = 0.001), level of blood CMV viral load (OR 1.53; 95% CI 1.24-1.89, p < 0.001), and level of blood ADV viral load (OR 1.56; 95% CI 1.05-2.32, p = 0.027). Higher probability of developing viral disease was strongly associated with more types of virus detected in blood (p < 0.001). Significant difference in the causes of death was observed among patients with and without viral co-infection (p = 0.014). Infection (87.5%) was the major cause of death of patients with viral co-infection, whereas relapse of hematologic disease (70%) was the major cause of death of patients with mono-viral infection. Viral co-infection is a common and significant infectious complication in pediatric recipients of allo-HSCT. Blood monitoring of CMV, ADV, and BKV is suggested among pediatric patients who develop GvHD or who have rising of CMV or ADV viremia following allo-HSCT. © 2010 John Wiley & Sons A/S.